Fabrication and Performance Evaluation of Rice-Straw Lignocellulosic Filters for Particulate Matter Removal from Air - Gurleen Kaur; Simrandeep Kaur (Sriwijaya Journal of Environment, 2026)
Background: Ambient particulate matter (PM) is the leading environmental health risk worldwide, yet conventional polypropylene and fiberglass filters are fossil-derived and non-biodegradable, while open burning of crop residues remains a major regional PM source. Objective: This study fabricated biodegradable air filters from post-harvest rice-straw lignocellulose using a simple, binder-free sequential treatment and evaluated their particulate filtration performance. Methods: Rice straw was treated sequentially with 1% NaOH, 3% H2O2, and 1% H2SO4, neutralized, molded, and dried, then characterized by scanning electron microscopy, Fourier-transform infrared spectroscopy, and liquid-displacement porosimetry, and tested in a custom wind tunnel against an incense-smoke challenge at face velocities of 0.1-1.0 m s-1. Linear and quadratic regression, Pearson correlation, and one-way ANOVA with effect sizes were applied. Results: The treatments produced a hierarchically porous microfibrous network with 88.5% porosity. At 0.5 m s-1 the filter removed 96.5 ± 0.8% of PM2.5 and 98.2 ± 0.5% of PM10 at only 45 ± 2.0 Pa, giving a Quality Factor of 0.074 Pa-1. Efficiency fell and resistance rose with face velocity (R2 = 0.945-0.995; ANOVA p < 0.001; η2 > 0.95). Single-pass output met both WHO 2021 and Indonesian PP 22/2021 PM2.5 limits. Conclusion: Rice-straw lignocellulosic filters offer a low-cost, biodegradable, and policy-relevant route to particulate control that simultaneously valorizes an open-burning agricultural residue.